Occurrence and molecular characterization of Bartonella spp. and hemoplasmas in neotropical primates from Brazilian Amazon - Bonato, Letícia [UNESP]; Figueiredo, Mayra Araguaia Pereira [UNESP]; Gonçalves, Luiz Ricardo [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Elsevier, 2015)
Little is known about the prevalence and genetic diversity of Bartonella spp. and hemoplasmas in nonhuman primates (NHP). The present study aimed to investigate the occurrence of and assess the phylogenetic position of Bartonella spp. and hemoplasma species infecting neotropical NHP from Brazilian Amazon. From 2009 to 2013, a total of 98 blood samples from NHP belonging to the Family Cebidae were collected in the island of São Luís, state of Maranhão, of which 87 NHP were from Wild Animal Screening Center (CETAS) in the municipality of São Luís, and 11 (9 Sapajus sp. and 2 Saimiri sciureus) were from NHP caught in the Sítio Aguahy Private Reserve. DNA samples were screened by previously described PCR protocols for amplifying Bartonella spp. and Mycoplasma spp. based on nuoG, gltA and 16S rRNA genes, respectively. Purified amplicons were submitted to sequencing and phylogenetic analysis. Bacteremia with one or more Bartonella spp. was not detected in NHP. Conversely, 35 NHP were PCR positive to Mycoplasma spp. The Blastn analysis of seven positive randomly selected sequencing products showed percentage of identity ranging from 95% to 99% with other primates hemoplasmas. The Maximum Likelihood phylogenetic analysis based on a 1510. bp of 16S rRNA gene showed the presence of two distinct clusters, positioned within Mycoplasma haemofelis and Mycoplasma suis groups. The phylogenetic assessment suggests the presence of a novel hemoplasma species in NHP from the Brazilian Amazon.
Keywords: Amazon; Bartonella spp.; Brazil; Hemotropic mycoplasmas; Monkeys